Feminine words in Jordan - Al Jarrah, Lina Ali (Journal of Humanities & Social Sciences, 2017)
The aim of this research is to apply the theory of semantic fields to the words of feminine media in modern times, in a spatial and temporal framework, to highlight linguistic, semantic, social and cultural aspects. The researcher chose the collection of feminine words in Jordan in the 21st century. A sample of this study, the names of the graduates of Yarmouk University, was chosen in 2016. It was necessary to frame the study in a selected sample because it is not in the ability of a person to remember the names of all people all of them. Since the research is an application of the semantic field theory - one of the modern linguistic theories - it was necessary before the search of the words of the flags to show a brief overview of that theory, in terms of concept, origin, and historical roots.